Myeloid-driven immunosuppression in head and neck cancer: single-cell ATAC/RNA and spatial transcriptomic perspectives - Luo, Rui; Yang, Jianzheng; Cao, Zimeng; Li, Bing (Frontiers in Oncology, 2025)
Head and neck squamous cell carcinoma (HNSCC) remains a prevalent epithelial malignancy. Immune-checkpoint inhibitors have reshaped first-line therapy for recurrent/metastatic disease; yet durable benefit is confined to a subset, reflecting myeloid-centric mechanisms—SPP1+ TAM barriers, cDC1/IL-12 insufficiency, and CXCL8–CXCR1/2–driven neutrophil trafficking—distinct from, and complementary to, classical lymphoid exhaustion. In this review we summarize advances from single-cell RNA and ATAC profiling and spatial transcriptomics that resolve macrophage, dendritic-cell and neutrophil programs, and appraise translational opportunities spanning myeloid reprogramming, innate–adaptive combinations and spatial biomarkers. We also discuss enduring challenges—including HPV-status heterogeneity, limited assay standardization and a scarcity of predictive metrics—that temper implementation. By integrating myeloid-informed readouts (e.g., SPP1–TAM burden, cDC1 competency, serum IL-8) with PD-1–based regimens, EGFR-directed antibodies and myeloid checkpoints (CD47–SIRPα, PI3Kγ, CXCR1/2), emerging strategies aim to restore antigen presentation, improve lymphocyte trafficking and remodel tumor–stroma interfaces. Our synthesis provides an appraisal of the evolving landscape of myeloid-informed precision immuno-oncology in HNSCC and outlines pragmatic standards and avenues for clinical translation. We hope these insights will assist researchers and clinicians as they endeavor to implement more effective, individualized regimens.